Conservation of archaeological sites in the face of urban sprawl: the case of Independencia, Peru - Cleber Dionis; Mirtha Cristobal; Natalia Álvarez; Cristian Yarasca-Aybar (My University, 2025)
Abstract In Lima (the capital of Peru), archaeological sites are constantly being threatened by accelerated urban expansion. This study examines Independencia (a district in northern Lima), where 95% of archaeological areas have been encroached upon due to inadequate planning and conservation policies. Focusing on four key archaeological sites (Cerro La Cruz, Cerro San Jerónimo, Pampa de Cueva, and San Jerónimo), this study employed a comprehensive pathological analysis to assess the extent and causes of deterioration. Data were gathered through field observation sheets based on the Ministry of Culture’s Conservation Guide, alongside historical photographs, aerial imagery, and urban mapping. The results indicate that human agents (27.1%) are the primary drivers of damage, supplemented by fortuitous (4.07%) and biological (2.89%) agents. The pronounced deterioration, particularly from human agents, underscores the urgent need for a holistic conservation strategy that integrates community participation with technical heritage management, ensuring that Lima’s pre-Hispanic legacy is preserved amidst ongoing urban pressure.
Keywords: Urban sprawl; Architecture; Face (sociological concept); Geography; Archaeology; History; Urban planning; Sociology; Civil engineering; Engineering; Social science; Urban sprawl; Architecture; Face (sociological concept); Geography; Archaeology; History; Urban planning; Sociology; Civil engineering; Engineering; Social science; Social Sciences Social Sciences Cultural Studies Archaeology and Cultural Heritage; Social Sciences Arts and Humanities Archeology Cultural Heritage Management and Preservation; Social Sciences Social Sciences Cultural Studies Urbanism, Landscape, and Tourism Studies